2022
DOI: 10.1038/s41598-022-08352-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy and multispectral imaging for fingerprinting of aflatoxin-B1 contaminated (Zea mays L.) seeds: a preliminary study

Abstract: Cereal seeds safety may be compromised by the presence of toxic contaminants, such as aflatoxins. Besides being carcinogenic, they have other adverse health effects on humans and animals. In this preliminary study, we used two non-invasive optical techniques, optical fiber fluorescence spectroscopy and multispectral imaging (MSI), for discrimination of maize seeds naturally contaminated with aflatoxin B1 (AFB1) from the uncontaminated seeds. The AFB1-contaminated seeds exhibited a red shift of the emission max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…UV fluorescence has also been used for aflatoxin detection in other agricultural products. A recent study [ 18 ] using UV fluorescence spectra for maize kernel aflatoxin detection corroborated an earlier study [ 15 ] by finding a similar fluorescent shift associated with aflatoxin-contaminated kernels. The study reported a classification accuracy of 100% with principal component and linear discriminant analyses.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…UV fluorescence has also been used for aflatoxin detection in other agricultural products. A recent study [ 18 ] using UV fluorescence spectra for maize kernel aflatoxin detection corroborated an earlier study [ 15 ] by finding a similar fluorescent shift associated with aflatoxin-contaminated kernels. The study reported a classification accuracy of 100% with principal component and linear discriminant analyses.…”
Section: Introductionsupporting
confidence: 70%
“…One of the more recent developments in the detection of aflatoxin contamination is the use of spectral technology, including the use of fiber-optic spectrometry [ 14 ], fluorescence hyperspectral imaging [ 15 ], multispectral imaging [ 11 , 16 ], fluorescence spectroscopy [ 17 ], fluorescence spectroscopy and multispectral imaging [ 18 ], ultraviolet–visible–near-infrared spectra [ 19 ], and hyperspectral and microscopic imaging [ 20 ]. A fluorescence hyperspectral study [ 15 ] found that there exists a fluorescence shift toward longer wavelengths in the blue-green spectral region in fungal-infected maize kernels with high aflatoxin content.…”
Section: Introductionmentioning
confidence: 99%
“…The system is equipped with a 450 W high-pressure Xe lamp and a photomultiplier tube. After excitation at 337 nm, fluorescence emission spectra of pollen samples were recorded in the range from 350 to 800 nm with 1 nm spectral resolution using a quartz optical fiber (4 mm effective diameter) at a distance of 2 mm 58 , 59 . Both slits were fixed at 3 nm for excitation and emission beams, and the integration time was 0.1 s. Each sample representing bulk pollen of one class was measured 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…The system is equipped with a 450 W high-pressure Xe lamp and a photomultiplier tube. After excitation at 337 nm, fluorescence emission spectra of pollen samples were recorded in the range from 350 to 800 nm with 1 nm spectral resolution using a quartz optical fiber (4 mm effective diameter) at a distance of 2 mm 48,49 . Both slits were fixed at 3 nm for excitation and emission beams, and the integration time was 0.1 s. Each sample representing bulk pollen of one class was measured 3 times.…”
Section: Collection Of Pollen and Measurementsmentioning
confidence: 99%